Acalculous cholecystitis in the setting of immunoglobulin a vasculitis: a case report with literature review - Burruss, Clayton Prakash; Bacus, Ioana; Utamsingh, Pooja Dushyant (International Journal of Contemporary Pediatrics, 2022)
Immunoglobulin A vasculitis (IgAV), also known as Henoch-Schönlein Purpura, is the most common childhood vasculitis which presents with a tetrad of symptoms: palpable purpura, abdominal pain, arthralgias, and renal involvement. Gastrointestinal involvement has been reported with findings including abdominal pain, pancreatitis, intussusception, ischemia, and gallbladder involvement. Our patient had the classical presentation of IgAV with additional gallbladder thickening found on imaging. He was managed conservatively for his symptoms and gallbladder thickening. This case adds to the six prior cases that we found in our literature search reported of gallbladder thickening alongside IgAV. However, this was the only case that was managed conservatively resulting in a complete resolution of symptoms.